ISSUES OF INCREASING THE OPERATIONAL RELIABILITY OF EXISTING BUILDINGS AND STRUCTURES (Spectrum Journal of Innovation, Reforms and Development, 2022)
In the article, very important problems are the quality of existing buildings and structures, their reliability, durability, durability, durability. Information is provided on measures to eliminate damage and raids caused by deformations in buildings and structures in operation, to improve the reliability of buildings.